Pemeriksaan Kehamilan dan Edukasi Pencegahan DBD pada Ibu Hamil - Evi Wulandari; Asmuni, Asmuni (Jurnal Pengabdian Bidang Kesehatan, 2025)
Complications of pregnancy and childbirth as the highest cause of maternal mortality can be prevented by examining pregnancy through regular ANC Antenatal service standards include conducting physical examinations including inspection, palpation and auscultation. In addition to physical examination, counseling and counseling is one of the standards in antenatal care (Ministry of Health, 2020). The high incidence of dengue hemorrhagic fever (DHF) in West Sulawesi makes it very necessary to provide education on the prevention of DHF in pregnant women because dengue infection in pregnancy can cause the risk of bleeding for the mother. Community service activities aim to increase the knowledge of pregnant women about fetal development so as to minimize the incidence of emergencies in pregnancy and increase awareness of dengue fever mosquito breeding. Dengue fever infection in pregnancy. The implementation method includes an approach in the form of a pregnancy examination and providing education related to dengue fever prevention. The results of community service activities show that on May 10, 2025, pregnancy checks were carried out for 10 pregnant women and education related to dengue fever prevention was provided.